The value of privacy for people with dementia - Buhr, Eike; Schweda, Mark (Frontiers in Psychiatry, 2025)
Introduction The concept of privacy marks an astonishing gap in the discussion about care for people with dementia (PwD). In general, questions of privacy play an important role and attract much attention in the ethics of nursing care. Yet, when it comes to dementia care, there is hardly any systematic ethical debate on the topic at all. It almost seems as though PwD lost any plausible interest in privacy and no longer had a private sphere that needed to be considered or protected. However, this not only contradicts widespread moral intuitions but also ignores the views and needs of those affected. Arguments This conceptual analysis sets out to explore the value of privacy for PwD. We first outline the origins and dimensions of the concept of privacy itself and point out problems and limitations in the context of dementia. Especially the prevalent liberal conceptions’ dependence on the idea of individual autonomy poses considerable challenges to an adequate understanding of the moral significance of privacy for PwD. Therefore, we subsequently examine alternative ways of conceptualizing the value of privacy in the context of dementia care. Conclusion We argue that autonomy-based concepts of privacy may still apply in the early stages of dementia. In the further course of the syndrome, however, the relevance of other normative aspects comes to the fore, especially respect for remaining personal preferences as well as objective criteria of dignity and well-being. Thus, we outline in a differentiated way how and to what extent privacy can be of normative importance even beyond the purview of autonomy and should consequently be considered in dementia care.